1990
DOI: 10.1097/00132582-199010000-00020
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diltiazem on the Cardiovascular Response to Tracheal Intubation

Abstract: The eficacy of diltiazem in the attenuation ofthe cardiovascular response to laryngoscopy and tracheal intubation was studied in patients who received 0.2 or 0.3 mg/kg diltiazem 60 seconds before the start of laryngoscopy. These data were cornpared with a control group who received saline. Each group consisted of I0 patients who had elective surgery. Patients who received saline showed a sign$cant increase in mean arterial pressure and rate pressure product associated with tracheal intubation. These increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…2 It has also been reported that MAP starts to decrease 20-40 sec after diltiazem /v administration and is maximal at 1.5 min. 4 The MAP begins to increase about 15 see after layrngoscopy and attains a maximum value at~r 30-45 see ff no pretreatment is given. 7 Thus,/v nicardipine or diltiazem should be given 60 see before laryngoscopy to attenuate the pressor responses in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…2 It has also been reported that MAP starts to decrease 20-40 sec after diltiazem /v administration and is maximal at 1.5 min. 4 The MAP begins to increase about 15 see after layrngoscopy and attains a maximum value at~r 30-45 see ff no pretreatment is given. 7 Thus,/v nicardipine or diltiazem should be given 60 see before laryngoscopy to attenuate the pressor responses in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…15,16 Different pharmacologic agents like lidocaine, vasodilator agents inhibiting sympathoadrenal response, α and β adrenergic blockers, and opioids can be administered prior to tracheal intubation in order to prevent haemodynamic responses (Helfman et al; Mikawa et al). 4,17 In present study at baseline all the groups were matched for haemodynamic parameters and did not show a significant intergroup difference. However, immediately after injection of test drug (1 minute after test drug) both the test groups showed a significant decrease in SBP (systolic blood pressure) and heart rate.…”
Section: Discussionmentioning
confidence: 67%
“…8 Pharmacological measures using volatile anesthetics-to deepen the anaesthesia, topical or intravenous lignocaine opioid analgesics like fentanyl, magnesium sulphate, calcium channel blockers beta-blockers clonidine and vasodilators-sodium-nitroprusside, nitro-glycerine have been studied, but none of the above approaches have proved to be ideal due to their limitations and side effects. [9][10][11][12][13][14] Hence the search of an ideal agent to attenuate the hemodynamic responses of laryngoscopy and intubation is still continuing.…”
Section: Introductionmentioning
confidence: 99%